Modelling outcome‐related risk in choice experiments1. (14th June 2013) - Glenk, Klaus; Colombo, Sergio
Abstract : In this study, we introduce information on outcome‐related risk as an additional attribute in a choice model of preferences for a land‐based climate change mitigation project. We provide a comprehensive comparison of different model specifications arising from different behavioural assumptions about the way that respondents process information on outcome‐related risk within the choice task. We find significant differences between several specifications in terms of both model fit and WTP estimates. The behavioural assumptions made when choosing a particular model specification, and reasons that motivate them should be made explicit, and consequences of using different specifications should not be ignored.